A Design of the Compression Chamber and Optimization of the Sealing of a Novel Rotary Internal Combustion Engine Using CFD - Savvas Savvakis; Dimitrios Mertzis; Elias Nassiopoulos; Zissis Samaras (Energies, 2020)
The current paper investigates two particular features of a novel rotary split engine. This internal combustion engine incorporates a number of positive advantages in comparison to conventional reciprocating piston engines. As a split engine, it is characterized by a significant difference between the expansion and compression ratios, the former being higher. The processes are decoupled and take place simultaneously, in different chambers and on the different sides of the rotating pistons. Initially, a brief description of the engine’s structure and operating principle is provided. Next, the configuration of the compression chamber and the sealing system are examined. The numerical study is conducted using CFD simulation models, with the relevant assumptions and boundary conditions. Two parameters of the compression chamber were studied, the intake port design (initial and optimized) and the sealing system size (short and long). The best option was found to be the combination of the optimized intake port design with the short seal, in order to keep the compression chamber as close as possible to the engine shaft. A more detailed study of the sealing system included different labyrinth geometries. It was found that the stepped labyrinth achieves the highest sealing efficiency.